Treino da oralidade na aula de PLE: uma experiência com conversas informais no nível A - Duarte, Isabel Margarida (2018)
Spoken language training in Portuguese as a Foreign Language class: an informal conversation experience at level A. The starting point of this paper are difficulties in listening in Portuguese as a Foreign/Second Language classes, especially at beginner levels. Using previous research carried out at the MA in Portuguese as Second/ Foreign Language at University of Oporto, we identified some barriers in listening. Difficulties stem either from characteristics of informal conversation or from particularities of European Portuguese. We selected transcribed informal conversations, whose topic is adequate to A level classes. Then we isolated some possible obstacles in understanding informal conversations that we consider feasible for this level of proficiency. To test the hypotheses formulated, a non-real but plausible conversation was produced, using some of the structures taken from the transcriptions of the oral corpus.